PROBLEMS WITH SECTION TWO TOEFL PREDICTION TEST - Friska, Yuliana; Syafi'i, Moh. Thoyib (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
The purpose of this study was to determine (1) the difficulties students faced in Section 2 of the TOEFL Prediction Test and (2) the reason why they consider those topics were difficult. A mixed method design was used in this study. A total of 30 students from different majors at Pamulang University were the test sample to determine difficulties faced by the students. Semi-structured interviews with the five low-performing participants who recorded the most errors on the test to explore the reasons. Results indicated reduced clause (20%) was the most difficult questions to students, followed by subject-verb agreement (13%), parallel structures (13%), comparisons (13%), pronouns (9%), and coordinating conjunctions (9%). It was also found Part B to be more difficult than Part A because it was harder to spot the mistakes in a sentence than it was to complete the sentence from multiple choices. Additionally, the results also revealed that reasons affecting the difficulties in answering the topics namely lack of knowledge and preparation, time management, and lack of vocabularies. Therefore, TOEFL teachers and trainers are strongly encouraged to pay more attention to the six topic study exercises with the highest error percentage, and to train students with various exercises in order to get used to the actual test.